Hydraulic resistance to overland flow governed by Froude number on semi-arid hillslopes under shrubs and crops. Issue 10 (27th July 2021) - Cantalice, Jose Ramon B.; Dias, I. C. G. M.; Andrade, D. S.; Assis Filho, F. M.; Souza, W. L. S.; Nunes, E. O. S.; Guerra, S. M. S.; Silva Junior, V. P.; Sartori, L.; Freitas, F. J.; Cavalcante, D. M.; de Sousa Lima, José Romualdo; et al.
ABSTRACT: Overland flow occurs on a land surface, making a sheet flow without any flow concentration. Under these conditions, cultivated semi-arid hillslopes experience inter-rill erosion. One objective of this study was to evaluate the hydraulic resistance caused by semi-arid crops and shrubs in two slopes' field conditions, and the other was to learen more about the overland flow governed by Froude number. To achieve these targets, a set of rainfall simulations was performed on two slope gradients, of 4.9% and 8.9%, covered by shrubs and semi-arid crops. On these two semi-arid hillslopes, exfiltration occurred, which added flow from subsurface water by seepage. We show, for the first time, that for overland flow with Reynolds number from 1 to 100 in different crops and native Brazilian shrub, hydraulic resistance is more strongly correlated with Froude number than with Reynolds number, as were the vegetal force drag and the soil detachment rate.